Alzheimer´s Disease associated with Psychiatric Comorbidities - Garcez,Michelle L. (2015)
Alzheimer's disease (AD) is the most common cause of dementia and has become a severe public health issue. It is estimated that globally, 35.6% of people have some form of dementia. This number is expected to double by 2030, and possibly even triple by 2050. The disease is associated with deficits in cognition/memory and a reduced ability in coping with everyday life. Moreover, patients can experience behavioral alterations such as mood swings, depression and hallucinations. Therefore, it is common to find the presence of neuropsychiatric comorbidities such as depression, schizophrenia and bipolar disorder during the course or development of AD. These disorders can become severe enough to interfere with the patients daily functioning, and can worsen the course of the disease. However, little is known about the causal relationship between psychiatric comorbidities and AD, or the reasons for the predisposition of some individuals to such disorders. Therefore, the purpose of this review is to clarify the causal relationship between depression, schizophrenia and bipolar disorder with AD.